Interrelationships Between Mathematics Anxiety, Mathematics Beliefs And Mathematics Teaching Efficacy Of Pre-Service Student Teachers - Irene, Tiong Xin Xin (Universiti Malaysia Sarawak (UNIMAS), 2009)
This research investigated the relationships between mathematics anxiety, mathematics beliefs and mathematics teaching efficacy of pre-service student teachers. Differences in mathematics teaching efficacy, mathematics anxiety and mathematics beliefs based on gender were also investigated. In addition, differences in mathematics teaching efficacy, mathematics anxiety and mathematics beliefs based on academic performance (CGPA and teaching practice grade) were investigated. The samples in this study consisted of 108 pre-service student teachers either from the Mathematics Education Programme or Computer Science Education Programme in the Faculty of Cognitive Sciences and Human Development at University of Malaysia Sarawak. Three research instruments were used to collect data namely Mathematics Anxiety Rating Scale-short version (MARS-S), Mathematics Teaching Efficacy Beliefs Instruments (MTEBI) and Domain Specific Beliefs Questionnaire (DSBQ). The research designs were crosssectional survey with correlational and comparative study. Pearson-product moment correlations were used to measure relationships between mathematics anxiety, mathematics teaching efficacy and mathematics beliefs. Independent ttest was used to determine the differences in mathematics teaching efficacy, mathematics anxiety and mathematics beliefs based on gender. One Way ANOVA was used to determine the differences in mathematics teaching efficacy, mathematics anxiety and mathematics beliefs based on academic performance (CGPA and teaching practice grade). The findings from the present study revealed significant difference in pre-service student teachers' mathematics anxiety based on academic performance (CGPA). In addition, significant positive relationships were found between mathematics anxiety and mathematics teaching efficacy, mathematics anxiety and mathematics beliefs, and mathematics beliefs and mathematics teaching efficacy.